2019
DOI: 10.1080/1331677x.2019.1642779
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability, market conditions and outreach: the vicious misconception of the win-win proposition in the microfinance industry

Abstract: The shift of the Microfinance Institutions (MFIs) from the povertylending approach to the financial system approach is likely to have two counterbalancing effects on the social mission of poverty alleviation and women empowerment. On the one handand as is desirablefinancial sustainability could cause MFIs to increase the depth and breadth of their outreach. But on the other handand possibly at the cost of the social missionfinancial sustainability may become the core objective of the MFIs. The aim of this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…For instance, the studies [14,39] found no evidence of a trade-off between social and financial efficiency. In contrast, the study of Ullah et al [41] found a clear trade-off between the two efficiency measures. The study [41], however, included the MFIs from all six regions of the world in the Sample.…”
Section: Relevant Literaturementioning
confidence: 77%
See 2 more Smart Citations
“…For instance, the studies [14,39] found no evidence of a trade-off between social and financial efficiency. In contrast, the study of Ullah et al [41] found a clear trade-off between the two efficiency measures. The study [41], however, included the MFIs from all six regions of the world in the Sample.…”
Section: Relevant Literaturementioning
confidence: 77%
“…In contrast, the study of Ullah et al [41] found a clear trade-off between the two efficiency measures. The study [41], however, included the MFIs from all six regions of the world in the Sample.…”
Section: Relevant Literaturementioning
confidence: 77%
See 1 more Smart Citation
“…It has also been proven empirically that microfinance plays a vivid role in transforming the lives of the poor, particularly women dwelling in rural areas. However, the system is also faced with challenges such as mission drift, multiple borrowing and financial sustainability, etc., thereby generating concerns for policymakers and academics (Ullah et al. , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, MFIs need to achieve efficiency in their operations for an uninterrupted flow of financial services to the masses (Ullah et al, 2019). Nonetheless, attaining efficiency becomes crucial in the current context because donors, funders and investors now require MFIs to be self-sustainable, and operate without donations or concessionary funds as these sources have become insufficient.…”
Section: Introductionmentioning
confidence: 99%